Development and Evaluation of a Web-Based Dietary Assessment Tool (Foodbook24) for Use in a Chinese Population in Ireland. (7th June 2021) - Yang, Shuhua; Bennett, Grace; Bardon, Laura; Feeney, Emma; Gibney, Eileen
Abstract: Objectives: Foodbook24 is a web-based, self-administered 24-h dietary recall tool initially developed for the Irish adult population. However, the application of this tool to the Chinese population is limited. This study aims to describe the development of Foodbook24 for Chinese population and conduct user evaluations of the developed Foodbook24. Methods: Foodbook24 consists of different components including food list, food composition, portion size images alongside supplementary questionnaires such as demographic and evaluation questionnaire. Food items from China Food Composition Tables and Chinese grocery shops in Dublin, Ireland were used to expand the food list. Food composition data were derived from the Composition of Foods Integrated Dataset UK (CoFID), and China Food Composition Tables. Portion sizes of new foods were derived by determined mean reported intakes from the China Health and Nutrition Survey, and/or packaged portions of specific foods. All components were then translated to Chinese. Acceptability of the developed tool was assessed by n  = 20 participants, Chinese aged 18 and over living in Ireland, following a traditional Chinese diet. Participants were asked to complete a food reflection, using a Pinterest board, whereby participants were asked to post photos of commonly consumed foods. This image board was then described by the participant using voice recording. The usability of the developed tool was assessed through 2 24 h dietary recalls using the developed Foodbook24 and a tool evaluation questionnaire. Results: 383 new foods with compositions were added to Foodbook24's original food list. 82 additional portion size images were created. Examination of participants' likeability and compatibility with the tool is currently ongoing, and foods identified within the acceptability study will be added to the tool. Conclusions: The use and applicability of novel dietary assessment tools, such as Foodbook24, need to be considered in all population groups in any given country, with wide and diverse eating habits. All elements (food list, portion size, food photos and language) need to be evaluated and considered before use to examine dietary intakes within an entire population. Funding Sources: China Scholarship Council.